Routine ribosomal PCR and DNA sequencing for detection and identification of bacteria. (July 2010) - Kemp, Michael; Jensen, Kristine H; Dargis, Rimtas; Christensen, Jens Jørgen
Detection and identification of bacteria by PCR and DNA sequencing from clinical sample material has been introduced as a diagnostic routine analysis during the last 5–10 years. Assays analyzing ribosomal genes have been found to be particularly useful. The technique has identified unusual bacteria as well as well-known bacteria in unusual infectious foci. Thereby, it has proven its value both in diagnosing infections in individual patients and as a tool to establish the pathogenic potential of bacteria not previously associated with disease. To be of clinical relevance, results from ribosomal PCR and DNA sequencing must be obtained fast and at acceptable costs. Processing of a high number of samples by individual laboratories can ensure both speed and low price. By continued technical development and further investigations of its usefulness in various clinical settings ribosomal DNA sequencing will most probably become as common a part of clinical bacteriology as culture is today.